2022
DOI: 10.1186/s13023-022-02587-0
|View full text |Cite|
|
Sign up to set email alerts
|

Long-term safety and clinical outcomes of olipudase alfa enzyme replacement therapy in pediatric patients with acid sphingomyelinase deficiency: two-year results

Abstract: Background Olipudase alfa is a recombinant human acid sphingomyelinase (ASM) enzyme replacement therapy (ERT) for non-central-nervous-system manifestations of acid sphingomyelinase deficiency (ASMD). We report 2-year cumulative safety and efficacy data after olipudase alfa treatment in 20 children (four adolescents [12–17 year], nine children [6–11 year], and seven infants/early child [1–5 year]) with baseline splenomegaly and growth deficits who completed the 1-year ASCEND-Peds clinical trial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 34 publications
0
18
0
Order By: Relevance
“…One-year results indicate good tolerability of the drug and clinically meaningful improvements. Two-year results showing continuing benefits from the first to second years for children has been reported as well [ 27 ]. However, no data outside of clinical trials have been reported yet.…”
Section: Discussionmentioning
confidence: 98%
“…One-year results indicate good tolerability of the drug and clinically meaningful improvements. Two-year results showing continuing benefits from the first to second years for children has been reported as well [ 27 ]. However, no data outside of clinical trials have been reported yet.…”
Section: Discussionmentioning
confidence: 98%
“…The improvements in clinical disease measures were consistent with those reported in other olipudase alfa trials in adults and children with chronic ASMD [ 8 , 9 , 11 13 ]. Adults receiving 2 years of olipudase alfa treatment had continued improvement and, in some cases, normalization of clinical manifestations over time, which has also been demonstrated in the pediatric population after 2 years of treatment [ 12 ] and for five adults receiving olipudase alfa for 6.5 years [ 13 ]. Overall, individuals had improvements in clinical measures of ASMD irrespective of baseline severity, as shown by individual responses, and improvements persisted or continued in the second year of treatment.…”
Section: Discussionmentioning
confidence: 85%
“…Importantly, hypersensitivity reactions including anaphylaxis occurred in some paediatric patients. In summary, olipudase alfa was well-tolerated in children and adults and, after treatment (1 year in adult and 2 years in children), resulted in improved lung function, reductions in spleen and liver volumes, improved platelet counts and lipid profiles, reductions in disease biomarkers, and improved growth (in children) [ 85 , 86 , 127 129 ].…”
Section: Managementmentioning
confidence: 99%